ANALISIS PENERAPAN SAK EMKM PADA UMKM SEKTOR PANGAN DI KECAMATAN MUARO BULIAN KABUPATEN BATANGHARI (Studi Pada Rumah Makan Putri Solo) - Chayrani Pebdayanti; Putri Apria Ningsih; Muthmainnah (CV. Aksara Global Akademia, 2024)
The purpose of this research is to find out what records are carried out by Micro, Small and Medium Enterprises in preparing their financial reports and to find out the preparation of financial reports using SAK EMKM for Micro, Small and Medium Enterprises. The method used is a qualitative descriptive method. The results of this research are that MSMEs at Putri Solo Restaurant do not keep records or bookkeeping regarding the entry and exit of financial reports and MSMEs at Putri Solo Restaurant do not record their financial reports in accordance with financial accounting standards for micro, small and medium entities (SAK EMKM). They only rely on memory to measure the amount of expenditure on production activities and these MSMEs also believe that their business does not need to record financial reports according to applicable standards.